The Effectiveness of the Balanced Scorecard Method in Supporting Comprehensive Performance in the Tana Toraja Regional Public Hospital - Rahma Gusmawati Tammu; Astriwati Biringkanae (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Malang, 2021)
Public organizations need to carry out comprehensive performance measurements, considering that the main objective of public organizations is not only the financial aspect but also the service aspect for the community. The balanced scorecard is a performance measurement method that not only emphasizes quantitative-financial aspects, but also non-financial qualitative aspects, so it is very suitable to describe the performance of public organizations. This study aimed to analyze the effectiveness of the balanced scorecard in measuring the comprehensive performance of the Tana Toraja Regional Public Hospital. Balanced Scorecard includes four perspectives, namely financial perspective, customers, internal business processes, and growth and learning. The research method used is a descriptive quantitative method represented by the average value and the frequency distribution of the satisfaction level of each variable for the customer perspective, internal business processes, as well as growth and learning. Meanwhile, for the financial perspective used analysis of revenue growth, comparison of budget and revenue realization, and cost recovery rate. The results showed that the Balanced Scorecard was very effective in measuring the comprehensive performance of the Tana Toraja Hospital